Depression in Somatic Disorders: Is There a Beneficial Effect of Exercise? - Roeh, Astrid; Kirchner, Sophie K.; Malchow, Berend; Maurus, Isabel; Schmitt, Andrea; Falkai, Peter; Hasan, Alkomiet (Frontiers in Psychiatry, 2019)
Background: The beneficial effects of exercise training on depressive symptoms are well-established. In the past years, more research attention has been drawn to the specific effects of exercise training on depressive symptoms in somatically ill patients. This reviews aims at providing a comprehensive overview of the current findings and evidence of exercise interventions in somatic disorders to improve depressive symptoms. Methods: We systematically searched PubMed and Cochrane databases and extracted meta-analyses from somatically ill patients that underwent exercise interventions and provided information about the outcome of depressive symptoms. Results: Of the 4123 detected publications, 39 were selected for final analysis. Various diseases were included (breast-cancer, prostate cancer and mixed-cancer, cardiovascular disease, coronary heart disease, hemodialysis, fibromyalgia syndrome, acute leukemia, other haematological malignancies, heart failure, HIV, multiple sclerosis, mixed neurological disorders, Parkinson disease, stroke, ankylosing spondylitis, traumatic brain injury, lupus erythematodes). Most meta-analyses (33/39) found beneficial effects on depressive symptoms, but quality of the included studies as well as duration, intensity, frequency and type of exercise varied widely. Conclusion: Exercise training has the potential to improve depressive symptoms in patients with somatic disorders. For specific training recommendations, more high quality studies with structured exercise programs and better comparability are needed.